2018
DOI: 10.2495/air180021
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Assessment of Links Between Exposure to Noise and Air Pollution and Socioeconomic Status

Abstract: The health impacts of exposure to noise and air pollution are well-documented, however socioeconomic status (SES) can be a determinant in exposure, while at the same time influencing both individual susceptibility and resilience. The scope of the work presented here was undertaken under a specific contract to the European Environment Agency (EEA) to provide an assessment that may be directly incorporated into EEA's 2018 report exploring the linkages between SES in Europe and exposure to air and noise pollution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Another aim of this study was to investigate whether there are any inequalities in exposure to environmental noise pollution, low socioeconomic status and the burden of disease in the two study area cities. Although the linkages between noise exposure and low SES have been recognized (Cesaroni et al, 2010;Bocquier et al, 2013;Dale et al, 2015;Casey et al, 2017;Barnes et al, 2018), relatively few studies have explored the relationship between exposure to noise, low SES and health together. By exploring the burden of disease from environmental noise pollution, this research will aim to identify if there is any difference in how noise is managed in a large Canadian city, Toronto, and a smaller city, London.…”
Section: Objectives/ Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another aim of this study was to investigate whether there are any inequalities in exposure to environmental noise pollution, low socioeconomic status and the burden of disease in the two study area cities. Although the linkages between noise exposure and low SES have been recognized (Cesaroni et al, 2010;Bocquier et al, 2013;Dale et al, 2015;Casey et al, 2017;Barnes et al, 2018), relatively few studies have explored the relationship between exposure to noise, low SES and health together. By exploring the burden of disease from environmental noise pollution, this research will aim to identify if there is any difference in how noise is managed in a large Canadian city, Toronto, and a smaller city, London.…”
Section: Objectives/ Research Questionsmentioning
confidence: 99%
“…However, North American cities were designed with the car in mind, which could be why these studies found a different relationship between noise and socioeconomic status (Noland, 2009). Additionally, wealthier citizens who live in noisy areas have the ability to purchase noise mitigation technology to reduce the amount of noise in their homes (Barnes et al, 2018). While low socioeconomic status individuals lack the ability to purchases noise mitigation technology to help reduce exposure to noise in their home (Baum et al, 1999).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…According to statutory requirements (Barnes et al, 2018b), the UK Government leads on the UK's input to International and European legislation relating to air quality, with input from the Scottish Government, and the other devolved administrations. Linking to the requirements of the EU Directives, the latest Air Quality Strategy published in July 2007 (DEFRA, 2007) established the framework for air quality improvements across the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic status (SES) can also be a determinant of exposure. At the same time, SES is influencing both individual susceptibility and resilience [ 13 ].…”
Section: Introductionmentioning
confidence: 99%